2015
DOI: 10.1111/aas.12537
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival in patients suspected of disseminated intravascular coagulation

Abstract: Lowered AT and in particular PC activity was predictive of mortality risk upfront in critically ill patients suspected of acute DIC. Mortality in patients suspected of acute DIC increased progressively across the spectrum of the overt ISTH score and not only in those fulfilling overt DIC criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…It is possible that these differences might have contributed to the higher proportion of patients with DIC according to the JAAM score compared to the ISTH-score. A high DIC score has been shown to be associated with a high incidence of massive bleeding and mortality [ 2 , 25 , 26 ], and, as shown in our study, to be associated with a longer stay in the ICU [ 25 ]. We also found higher mortality of patients with DIC and higher DIC scores in non-survivors.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is possible that these differences might have contributed to the higher proportion of patients with DIC according to the JAAM score compared to the ISTH-score. A high DIC score has been shown to be associated with a high incidence of massive bleeding and mortality [ 2 , 25 , 26 ], and, as shown in our study, to be associated with a longer stay in the ICU [ 25 ]. We also found higher mortality of patients with DIC and higher DIC scores in non-survivors.…”
Section: Discussionsupporting
confidence: 70%
“…We also found higher mortality of patients with DIC and higher DIC scores in non-survivors. It has recently been suggested that the use of the fixed ISTH score of ≥5 misses many patients with life-threatening DIC [ 25 ]. To assign patients to DIC and overt DIC a score of ≥ 4 for JAAM and ≥5 for ISTH, respectively, at any time point during the 10 day period was used in our study and a similar strategy was used in a recent study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our dataset antiplasmin (another natural antifibrinolytic substance) was not measured due to analytical constraints. There are no data about the time course of antiplasmin activity in major trauma; however, it has to be synthesised within cells (like PAI-1), and in other conditions, it rises over days rather than hours 21. This study was carried out in a small sample and there were no patients with penetrating trauma (reflecting the normal UK major trauma population in 2004) so our results can only be definitely applied to blunt trauma.…”
Section: Discussionmentioning
confidence: 95%
“…62 In a large cohort of patients with sepsis and suspected DIC, reduced AT and PC levels were predictive of mortality, regardless of whether the patient met the ISTH criteria for overt DIC. 63 Other markers of various aspects of coagulation and fibrinolysis have also been studied, with promising results, including TAT, SF, TFPI, PAI-1, von Willebrand factor, and Adamts-13. 62 D-dimers, a component of the ISTH DIC scoring algorithm, and fibrin monomer have been proposed as individual predictive markers of DIC.…”
Section: Biomarkers For the Diagnosis And Follow-up Of Dicmentioning
confidence: 99%